PERJANJIAN JUAL BELI MELALUI INTERNET (E-COMMERCE) DITINJAU DARI ASPEK HUKUM PERDATA - Zuni Rusviana; Adi Suliantoro (Jurnal Ilmiah Dinamika Hukum, 2018)
Internet development causes the formation of a new world, every individual has the right and ability to interact with everyone who can prevent him. Perfect globalization connects the entire digital community, one of which is a business sector called E-COMMERCE.E-COMMERCE has a difference from conventional sale and purchase agreements and brings different legal consequences and there are also some problems that are not yet commonly describedthis is a problem that is not immediately anticipated to cause problems in the future. Based on the description, the research is carried out with the title: “SALE AND PURCHASE AGREEMENT VIA INTERNET E-COMMERCE IN TERMS OF CIVIL LAW ASPECTS”. The formulation of the problem in this study is: (1) What is the validity of the SELLING BUY agreement through the internet if it is involved with Article 1320 of the Civil Code? (2) What is the legal consequence if there is a default in the purchase agreement through the internet (E-COMMERCE)? (3) Solution if there is a default in buying transactions through the internet (E-COMMERCE)? The method used is a normative juridical approach. To approach the problem in this study the author uses descriptive analytical research specifications. Data collection uses secondary data. The method of presenting data in this study was carried out in a descriptive manner. The analysis used in this sketch is qualitative descriptive. The results of the study indicate: (1) The validity of the agreement through the internet must have the same validity as the agreement that can be proven and in accordance with the provisions in Article 1320 BW. (2) The legal consequences of wanprestasi are compensation. the wanprestasi can be in the form of agreement fulfillment, contract fulfillment and compensation, ordinary compensation, cancellation of the agreement.(3) Solution if there is a wanprestasi in the sale and purchase agreement through: Litigation, Non Litigation, online site (kredibel.co.id, lapor.go.id, cek rekening.id), report directly to the police station and report to the bank.